Responsiveness of Indian Tax Structure - Chandan Karki (Abhigyan, 2015)
The objective of this paper is to measure the responsiveness of tax structure and highlight economic and strategic implications of tax revenue collection in India with regard to India’s economic growth and development. Findings include analysis of tax revenues including both direct and indirect taxes as far as measuring tax buoyancy and elasticity is concerned and possible recommendations for future so as to carve out a voluntary taxpaying culture on a large scale in India. Since there is lack of reliable data on various exemptions and/or deductions as are available under Indian tax laws, the focus is on collections at Central level only. All stakeholders including government, corporate sector, regulatory bodies and citizens need clarity on elasticity and buoyancy estimates of tax revenue collection in India so as to undertake immediate measures to address to worsening fiscal situation in the country. In India, there is lack of research in the area of tax revenue collection. The paper measured buoyancy and elasticity of Indian tax structure and thereafter linked it to forecast future tax revenue collections. The study revealed surprising result for indirect taxes which are reporting responsiveness of unity. The excise duty which has huge tax base i.e manufacturing activities in India reported responsiveness of 1.2. The direct taxes found to be more responsive and reported elasticity of more than unity.